Increased levels of brain serotonin correlated with MMP-9 activity and IL-4 levels resulted in severe experimental autoimmune encephalomyelitis (EAE) in obese mice - Hasan, M.; Seo, J. -E.; 라하만; Kang, M. -J.; Jung, B. -H.; Kwon, O. -S. (Elsevier BV, 2016)
The aim of this study was to investigate the role of monoamine neurotransmitters on the severity of experimental autoimmune encephalomyelitis (EAE) in obese mice. EAE was induced in mice with normal diets (ND-EAE) and obese mice with high-fat diets (HFD-EAE) through the immune response to myelin oligodendrocyte glycoprotein (MOG) (35-55). The levels of dopamine (DA), serotonin (5-HT) and their metabolites in different anatomical brain regions were measured by high-performance liquid chromatography. The plasma and tissue NADPH oxidase and matrix metalloproteinases (MMP)-9 activities were analyzed by fluorescence spectrophotometry. The cumulative disease index and disease peaks were significantly higher in HFD-EAE compared with those in ND-EAE. Significantly higher 5-HT levels and lower 5-HT turnovers 5-hydroxyindole acetic acid ((5-HIAA)/5-HT) were found in the brains of HFD-EAE mice compared with those found in the HFD-CON and ND-EAE-mice brains. Moreover, increased DA levels were observed in the caudate nucleus of the HFD-EAE mice compared with the control and ND-EAE mice. The NADPH oxidase and MMP-9 activities in the plasma and tissues were significantly higher in both the ND-EAE and HFD-EAE groups than in their respective controls. The cytokine levels in the plasma, tissues, and cultured splenocytes were found to be significantly altered in EAE mice compared with control mice. Moreover, HFD-EAE mice exhibited significantly higher MMP-9 activity and lower IL-4 levels than ND-EAE mice and were significantly correlated with brain 5-HT levels. In conclusion, the increased 5-HT levels in the brain significantly correlated with MMP-9 activity and IL-4 levels play an important role in the exacerbation of disease severity in HFD-EAE mice. (C) 2016 IBRO. Published by Elsevier Ltd. All rights reserved.